ANALISIS PERLINDUNGAN HUKUM KONSUMEN ATAS KEHILANGAN BARANG DALAM TRANSAKSI E-COMMERCE YANG DIASURANSIKAN DI INDONESIA - Eunike Yannie Hendrowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
The development of e-commerce transactions in Indonesia has provided significant convenience for people in conducting online buying and selling activities. However, on the other hand, various problems have emerged, one of which is the loss of goods during the delivery process, even when the goods have been insured.This study aims to analyze the forms of legal protection for consumers, the responsibilities of the parties involved, and the legal remedies that can be pursued in the event of an insurance claim rejection. The research method used is normative juridical legal research, employing both statutory and case approaches.The results of the study indicate that consumer legal protection is regulated under Law Number 8 of 1999 on Consumer Protection, which obliges business actors to provide compensation for losses suffered by consumers. In addition, provisions in the Indonesian Civil Code and Insurance Law also regulate the responsibility of insurance companies in fulfilling claims.However, in practice, claim rejections that disadvantage consumers still frequently occur. Therefore, consumers may pursue dispute resolution through the Consumer Dispute Settlement Agency or through litigation in court.